MAKNA SIMBOLIK TRADISI ADAT TARDIDI PADA KELAHIRAN ANAK ETNIK BATAK TOBA DI KOTA DURI - Elsa Dwi Clarita; Noor Efni Salam (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Tardidi tradition is one of the Batak Toba ethnic culture. There's an aspect of symbolic and meaning need to be represent from attribute and people behavior from Tardidi tradition. Purpose of this research to understand symbolic situation, interaction of social product, and interpretation tardidi tradition to Batak Toba ethnic child in Duri City. This research method is qualitative and interaction symbolic approach. There a eight Informant for this research such 2 tradition leader, 4 actors of uncle that represent parents, aunt and 2 common society. The Result of this research, symbolic situation in tardidi tradition to ethnic batak toba child Duri City conduct physic and social object. The physic object involves (dekke mas), ulos parompa, boras sipir ni tondi, tumpak, jambar, dan pasahat parsituak na tonggi. The social object involves pray to parents form their child, aunt, uncle, and common society Batak Toba ethnic. Interpretation of tardidi tradition conduct opened and closed behavior. Keywords: Symbolic Meaning, Tardidi Tradition, Symbolic Interaction